VICTOR IVANOVICH MOSCVIN. TO THE BLESSED MEMORY OF A TEACHER (TO THE 100th ANNIVERSARY FROM BIRTHDAY) - V. A. Shalygin; D. D. Melnik (Бюллетень сибирской медицины, 2013)
Viktor Ivanovich Moskvin – largest children's surgeon, Professor, doctor of medical Sciences, the student of the founder of Siberian school of pediatric surgery of Professor I.S. Vengerovsky.